Using medical plastics in perfusion Medizinische kunststoffe in der kardiotechnik - Münch, Frank; Göen, Thomas (Kardiotechnik, 2019)
Medical plastics are common technical industrial materials that are processed into medical products for medical applications under clean room conditions to ensu-re the strictest purity. The main advantages of plastics are their elasticity, ease of pro-cessing and low density. Disadvantages include lower mechanical strength and time-dependent degradation, in addition to the potential exuding of adjuvants in in-situ application and limited sterilizability due to lower thermal stability. The term “medical plastic” primarily denotes biocompatibility as a characteristic. A medical plastic should in particular be bioresistant and biocompa-tible, especially in direct and indirect contact with the human organism. Medical plastics are resistant to human biological material and other medical media. Chemi-cal resistance is also essential when plastics come into contact with disinfectants and acids, as in a medical setting. In addi-tion, medical plastics may have antimicro-bial properties. Additives to plastics allow their optimization in order to meet specific medical requirements. Polycarbonate, polypropylene, polyure-thane, polyvinyl chloride and silicone are key materials used in the application area of ext-racorporeal systems. Extracorporeal circulation components made of plastics include oxy-genators, heat exchangers, filters, reservoirs, connectors, cannulas, tubing, and more. There is no such thing as “the” perfect plastic, so compromises are often unavo-idable in material design. For example, highly biocompatible materials are usu-ally characterized by a low mechanical strength. The European Commission and the FDA recommend that medical materials used should have no relevant disadvantages for the patient. In extracorpore-al circulation tubing systems, for example, plasticizer migration into the blood can be significantly reduced by selecting suitab-le substitutes such as tri-(2-ethylhexyl)tri-mellitate (TEHTM, TOTM).Accordingly, PVC with the additive TOTM seems to have the least toxic risk on the organism. Like the tunica intima in the human organism, new concepts for composite materials and surface-modified materials promise impro-ved compatibility for plastics.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Additives; Extracorporeal circulati-on; Medical plastics; Toxicity